Body size at birth and coronary heart disease-related hospital care in adult men – findings from the Helsinki Birth Cohort Study. (17th February 2017) - von Bonsdorff, Monika E.; von Bonsdorff, Mikaela B.; Martikainen, Janne; Salonen, Minna; Kajantie, Eero; Kautiainen, Hannu; Eriksson, Johan G.
Abstract: Aim: We investigated, among those who had been hospitalized at least once due to coronary heart disease (CHD), the relationship between ponderal index (PI, birthweight/length 3 ) at birth, a measure of thinness, and the age at first hospitalization due to CHD, the number of CHD-related hospital care episodes, and cost of CHD-related hospital care from young adulthood to old age. Methods and results: Data from the Helsinki Birth Cohort Study included 964 men born in Helsinki, Finland during 1934–1944, who had been hospitalized due to CHD and had birth anthropometrics data. PI (kg/m 3 ) was categorized into low (<25.0), medium (25.0–27.5), and high (>27.5). CHD-related hospital care data were available from 1971 to 2013. We observed an earlier onset of (p = .014 for linearity) and a higher rate of CHD-related hospital care episodes among those in the lowest PI group (incidence rate ratio: 1.35 [95% confidence interval: 1.16–1.59, p < .001]), compared to the highest PI group. CHD-related hospital care costs in the lowest PI group were 25% (p = .001, 4% to 46%) higher compared to those in the highest PI group. Discussion: Thinness at birth is associated with earlier onset, higher prevalence, and higher accumulated costs of CHD-related hospital in-patient care among men who developed CHD. KEY MESSAGES: Findings from this large birth cohort indicate that the onset of coronary heart disease (CHD)-related hospital in-patient care occurred at younger age during the 42-year time period among men who were born thin. Lower ponderal index (PI) was associated with a higher rate of CHD-related hospital in-patient care during the time period. We observed a linear increase in CHD-related hospital in-patient care costs across PI groups.